Human nature, ritual, and history: studies in Xunzi and Chinese philosophy - Cua, Antonio S. (Studies in philosophy and the history of philosophy, 2005)
"In this volume, distinguished philosopher Antonio S. Cua offers a collection of original studies on Xunzi, a leading classical Confucian thinker, and on other aspects of Chinese philosophy. While each essay individually makes an important contribution to the study of Chinese philosophy, the book as a whole represents a major scholarly achievement."--Jacket